Australian Slavonic and East European studies - Australasian Association for Study of the Socialist Countries.; Australian and New Zealand Slavists’ Association.; Australasian Association for the Study of the Socialist Countries.; University of Melbourne. Dept. of Russian and Language Studies.; University of Melbourne. Dept. of Russian.; Australasian Association for Communist and Post-Communist Studies. (Australian and New Zealand Slavists’ Association, 1987)
Continues Melbourne Slavonic studies.